2015
DOI: 10.1007/s00420-015-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China

Abstract: Several aspects of stressors were independent predictors of T2DM in a prospective cohort study in Tianjin, China. This practical information can be applied to the development of psychological interventions against T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
(53 reference statements)
1
19
1
Order By: Relevance
“…And a cohort study demonstrated that occupational stress was an independent predictor of diabetes. [11,35] Additionally, NAFLD is a hepatic manifestation of MetS (i.e., associated with those traditional risk factors). [32,36,37] Thus, we further analyzed the association between occupational stress and NAFLD after adjusted MetS-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…And a cohort study demonstrated that occupational stress was an independent predictor of diabetes. [11,35] Additionally, NAFLD is a hepatic manifestation of MetS (i.e., associated with those traditional risk factors). [32,36,37] Thus, we further analyzed the association between occupational stress and NAFLD after adjusted MetS-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…[9,11] A total of 6559 male police officers (aged 20–60 years) participated in the study; they received free health examinations, and completed the OSI-R questionnaire and interviewer-administered questionnaires. Among them, 4192 participants were excluded based on the following criteria: 408 did not complete the OSI-R and self-designed questionnaires at baseline; 295 had missing ultrasound scanning data; 981 had a history of or concurrent alcohol abuse (more than 30 g/d for males) [12] ; 362 were using steatohepatitis medication; 2146 had been diagnosed with NAFLD, chronic hepatitis B or C, autoimmune hepatitis or other liver diseases at the beginning of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations